2012
DOI: 10.1371/journal.pone.0034361
|View full text |Cite
|
Sign up to set email alerts
|

Isosteviol Has Beneficial Effects on Palmitate-Induced α-Cell Dysfunction and Gene Expression

Abstract: BackgroundLong-term exposure to high levels of fatty acids impairs insulin secretion and exaggerates glucagon secretion. The aim of this study was to explore if the antihyperglycemic agent, Isosteviol (ISV), is able to counteract palmitate-induced α-cell dysfunction and to influence α-cell gene expression.Methodology/Principal FindingsLong-term incubation studies with clonal α-TC1–6 cells were performed in the presence of 0.5 mM palmitate with or without ISV. We investigated effects on glucagon secretion, gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We have shown that ISV improves glucose and insulin sensitivity, lowers plasma triglycerides, lowers weight in diabetic KKAy mice, and markedly changes the gene expression profile of key insulin regulatory genes [ 33 , 34 ]. Additionally, we found evidence that ISV counteracts α-cell hypersecretion and contributes to changes in the expression of key genes after long-term exposure to palmitate [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that ISV improves glucose and insulin sensitivity, lowers plasma triglycerides, lowers weight in diabetic KKAy mice, and markedly changes the gene expression profile of key insulin regulatory genes [ 33 , 34 ]. Additionally, we found evidence that ISV counteracts α-cell hypersecretion and contributes to changes in the expression of key genes after long-term exposure to palmitate [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although AICAR increased MafB gene expression, it did not change glucagon hypersecretion to 5 mM leucine. Most recently we found that ISV decreased palmitateinduced hyperglucagonaemia in both the mouse islets and α-TC1-6 cells [53]. ISV 10 −6 M did not significantly decrease glucagon hypersecretion or change CHO content, TG content or α-cell proliferation to long-term leucine exposure.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, expression of Pdx1 , Nk6.1 , NeuroD1/B2 , HFN1α , HFN4α , and Foxa2 mRNA was decreased by 40–60%; these changes were reversible when hyperglycemia was corrected after 4 weeks but only partially after 14 weeks . In the db / db mouse model of T2D, chronic hyperglycemia also led to decreases in Nkx6.1 , NeuroD1/B2 , Pdx1 and Pax6 mRNA expression at 16 weeks, whereas HFN1α mRNA expression was unaffected . Furthermore, 24‐h exposure of human islets to a long‐chain fatty acid mixture resulted in marked reduction of Pdx1 and Pax6 expression …”
Section: Glucolipotoxicitymentioning
confidence: 93%